The Use of Literature in Language Teaching: A Pedagogical Approach from the Nepali Perspective - Regmi, Lok Raj (SCHOLARS: Journal of Arts & Humanities, 2022)
The use of literature in language teaching is still contentious though literature occupies limited space in the language syllabi. The language teachers assume that literature has less contribution to language teaching, believing that literary materials are challenging to handle in the classroom. However, I believe that literary materials are rich in content and have the creative language use to contribute to language teaching. In this juncture, this study analyzes the use of literature in English language teaching in general and the pedagogical approaches to be practiced in particular by using qualitative and analytical research design. For this purpose, the three texts of literature: Katherine Mansfield’s “The Garden Party” (story), Kamala Das’s “An Introduction” (poem), and Anton Chekhov’s The Cherry Orchard (drama) have been used as the primary texts to design the activities under three levels of interaction. These literary texts are analyzed to show the use and pedagogy of literature in language teaching. The study concludes that literature in language teaching contributes to the language development and aesthetic purpose. Exploring the literary texts involves students in (preliminary) interaction to draw the information of the text for conceptualization. Likewise, the activities under reading between the lines inculcate different skills in students such as discussing, analyzing, exploring and characterizing; and literary texts in beyond the text section involve students in aesthetic purpose-based activities in which students apply the critical lenses and create their own texts. This study provides many language teachers with insights to handle literary texts more effectively to sharpen students’ language, inferential and intellectual skills.